The Implementation of Discovery Learning for Reading Skill in EFL Classroom at SMPN 8 Padang - Nadya Zalviani; Yetti Zainil (Journal of English Language Teaching, 2021)
Many research about Discovery Learning revealed that implementing Discovery Learning in senior high school gave positive impact. Meanwhile, Curriculum also mentioned Discovery Learning as one of learning model. SMPN 8 Padang is one of excellent school in Padang City. English teachers there said that they implemented Discovery Learning in their teaching learning process. This research conducted to describe the implementation of Discovery Learning in junior high school. This research was a descriptive qualitative research. The sample was one of English teacher who taught in SMPN 8 Padang. The instruments were video recorder, observation checklist, and note-taking. The findings showed the teacher implemented six steps from preparation procedure of Discovery Learning and six steps from implementation procedure of Discovery Learning.